Reshaping Arbitration under the Changing Judicial Lens of Pakistan - Asim Arslan Ahmad (Social Science Review Archives, 2025)
Arbitration is considered as one of the best methods to settle the dispute through an informal way, outside the court. In Pakistan, although arbitration system is present yet there is no proper legislation to implement this system in the country as a substitute of litigation due to lack of proper procedure, conflict of laws and outdated nature of the supreme legislation on arbitration in the country, the Arbitration Act, 1940. The intervention of judiciary in enforcement of award has always been a challenge for arbitration in the country to take a proper place in the judicial structure of the country. The judicial trends regarding arbitration kept on changing and always created a challenge for the smooth running of arbitrational system. Until the Recognition and Enforcement Act, 2011, there was no thorough legislation for enforcement or recognition of a foreign arbitral award and there always have been a confusion regarding the seat of arbitration by Pakistani courts. The cultural differences and unawareness of society especially the unknowingness of legal fraternity has been an obstacle for arbitration in the country. The interpretation of Pakistani courts in the foreign arbitral awards is also questionable as the use of Public Policy as a ground for refusal of award under the banner of New York Convention, 1958 was not properly interpreted by the courts in certain cases.